2002
DOI: 10.1074/jbc.m202814200
|View full text |Cite
|
Sign up to set email alerts
|

Hsc66 Substrate Specificity Is Directed toward a Discrete Region of the Iron-Sulfur Cluster Template Protein IscU

Abstract: Hsc66 and Hsc20 comprise a specialized chaperone system important for the assembly of iron-sulfur clusters in Escherchia coli. Only a single substrate, the Fe/S template protein IscU, has been identified for the Hsc66/Hsc20 system, but the mechanism by which Hsc66 selectively binds IscU is unknown. We have investigated Hsc66 substrate specificity using phage display and a peptide array of IscU. Screening of a heptameric peptide phage display library revealed that Hsc66 prefers peptides with a centrally located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
129
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(131 citation statements)
references
References 44 publications
(79 reference statements)
2
129
0
Order By: Relevance
“…RecA and RecN have important roles in the repair of DNA damage which have been extensively characterized in UV damage experiments in many organisms, including E. coli and H. influenzae (43,50,51,77,82). Further repair mechanisms are potentially afforded by the gene products of NTHI0493 and NTHI0495, which encode homologues of the cochaperone proteins HscA and HscB, respectively, and that have roles in iron-sulfur cluster assembly (2,31,78). NTHI1588 is a homologue of a gene that encodes ImpA, an error-prone DNA polymerase originally identified in the incompatibility group plasmid TP110.…”
Section: Resultsmentioning
confidence: 99%
“…RecA and RecN have important roles in the repair of DNA damage which have been extensively characterized in UV damage experiments in many organisms, including E. coli and H. influenzae (43,50,51,77,82). Further repair mechanisms are potentially afforded by the gene products of NTHI0493 and NTHI0495, which encode homologues of the cochaperone proteins HscA and HscB, respectively, and that have roles in iron-sulfur cluster assembly (2,31,78). NTHI1588 is a homologue of a gene that encodes ImpA, an error-prone DNA polymerase originally identified in the incompatibility group plasmid TP110.…”
Section: Resultsmentioning
confidence: 99%
“…HscA and HscB function together as a nucleotide-dependent molecular chaperone system that is specific for IscU (15)(16)(17). HscA is a specialized member of the ubiquitous 70-kDa heat shock protein (Hsp70 or DnaK) family of molecular chaperones that facilitate protein folding, (dis)assembly and transport via nucleotide-dependent binding to unfolded, misfolded or unstable polypeptides in order to prevent non-specific aggregation processes (18).…”
mentioning
confidence: 99%
“…Recently, we found that Hsc66 interacts with cellulose-bound peptides containing a conserved motif of IscU (residues 99 -103, LPPVK), suggesting that Hsc66 binds a single discrete region of the protein (14). In addition, a synthetic peptide corresponding to IscU residues 98 -106 (ELPPVKIHC) was capable of eliciting IscU-like effects on Hsc66.…”
mentioning
confidence: 99%
“…In addition, a synthetic peptide corresponding to IscU residues 98 -106 (ELPPVKIHC) was capable of eliciting IscU-like effects on Hsc66. The Glu 98 -Cys 106 peptide stimulates Hsc66 ATPase activity with affinity similar to that of full-length IscU (14), whereas denatured proteins that bind Hsc66 but lack the LPPVK motif fail to stimulate Hsc66 ATPase activity (3). These results indicate that residues in the LPPVK motif play a key role in regulation of Hsc66 by IscU.…”
mentioning
confidence: 99%